Metal solubility in the rhizosphere of a co-cropping system. The role of total carbon exudation, soluble proteins and plant interaction. (June 2021) - Vergara Cid, Carolina; Oburger, Eva; Preiner, Julian; Pignata, María L.; Rodriguez, Judith H.
Abstract: In the present study we assessed how modified rhizosphere pH and root exudation (total carbon (C) and soluble proteins released) affected lead (Pb) solubility as well as plant growth and Pb accumulation. A pot experiment with Pb polluted agricultural soils was performed, which involved growing two species, Capsicum annum (pepper) and Tagetes minuta, with the latter being a native herb indicated as potential phytoextractor of Pb, in monocrop and co-cropping conditions. Changes in plant growth, metal uptake as well as rhizosphere soil parameters (pH, EC) and total C and protein exudation were determined. In addition, the metal extraction efficiency of exudates released under mono- and co-cropped conditions were investigated. Results showed that in contrast to the control soil (with low Pb concentration), total C exudation was higher in co-cropping systems in Pb contaminated soils which lead to increases in Pb uptake in both species. Exudates originating from T. minuta were more efficient in solubilizing Pb than exudates from pepper when grown under mono-cropping conditions. Exudates derived from co-cropping both species were either equally or less efficient in mobilizing Pb than exudates from T. minuta . The capacity of exudates to mobilize metals was dependent not only on the species specific quality of root exudates released, but also on its quantity, with the metal extraction efficiency increasing with C concentration in exudates. However, the role of exuded proteins in Pb solubilization was found to be negligible. Biochemical interactions in the rhizosphere under co-cropping conditions favored metal solubilization, and consequently Pb accumulation. The co-cropping conditions could allow accumulation of Pb to levels in pepper that pose risks when the plants are used as a food source. Graphical abstract: Image 1 Highlights: Carbon exudation was increased in co-cropping in Pb polluted soils. Carbon exudation played a major role in Pb, Cu, Zn, and Mn mobilization. Protein exudation was not related to Pb solubilization in soils. T. minuta root exudates were more efficient than C. annum to solubilize Pb in monocrop. Co-cropping affected growth and favored Pb accumulation in highly polluted soils.